2012
DOI: 10.1172/jci61405
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 neutralization improves chronic kidney disease–associated hyperparathyroidism yet increases mortality

Abstract: Chronic kidney disease-mineral and bone disorder (CKD-MBD) is associated with secondary hyperparathyroidism (HPT) and serum elevations in the phosphaturic hormone FGF23, which may be maladaptive and lead to increased morbidity and mortality. To determine the role of FGF23 in the pathogenesis of CKD-MBD and development of secondary HPT, we developed a monoclonal FGF23 antibody to evaluate the impact of chronic FGF23 neutralization on CKD-MBD, secondary HPT, and associated comorbidities in a rat model of CKD-MBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
252
1
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(280 citation statements)
references
References 46 publications
(49 reference statements)
8
252
1
11
Order By: Relevance
“…The pathophysiological impact of elevated FGF23 plasma levels is still ill-defined. While a high FGF23 plasma level is associated with high morbidity and mortality in heart and kidney failure [16][17][18], FGF23 neutralization increases the mortality of rats with chronic kidney disease-mineral and bone disorder [55]. In view of the present observations it is tempting to speculate that the association between the FGF23 plasma level and morbidity and mortality reflects the stimulating effect of aldosterone and/or NFκB on inflammation on the one side and FGF23 formation on the other, thus affecting both, FGF23 plasma level and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological impact of elevated FGF23 plasma levels is still ill-defined. While a high FGF23 plasma level is associated with high morbidity and mortality in heart and kidney failure [16][17][18], FGF23 neutralization increases the mortality of rats with chronic kidney disease-mineral and bone disorder [55]. In view of the present observations it is tempting to speculate that the association between the FGF23 plasma level and morbidity and mortality reflects the stimulating effect of aldosterone and/or NFκB on inflammation on the one side and FGF23 formation on the other, thus affecting both, FGF23 plasma level and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, mRNA FGF-23 as well as myocardial expression of the regulatory subunit of calcineurin and NFAT were higher in cases with LVH as compared with those without LVH (30). Of note, previous studies in experimental CKD have shown that complete inhibition of FGF-23 activity prevents the development of LVH and secondary hyperparathyroidism but it is associated with increased mortality linked to hyperphosphatemia and vascular calcifications [31]. These findings suggest that blocking FGFR4 or its downstream signaling pathways could represent a better therapeutic approach to reduce cardiovascular mortality in CKD patents.…”
mentioning
confidence: 77%
“…[1][2][3][4] As a common complication, CKD-MBD has now been received as one of the most important causes of vascular calcification and cardiovascular mortality in CKD patients. [5][6][7][8] In the previous decades, studies on the disturbances of miner and bone disorder in CKD-MBD were mainly focused on the derangement of calcium/phosphate homeostasis. [9][10][11] However, up until recently, since numerous studies have demonstrated that magnesium (Mg) played an important role in the pathophysiology of the cardiovascular system and its disorders were associated with an increased risk of cardiovascular morbidity and mortality, [12][13][14] the role and mechanism of magnesium homeostasis in CKD-MBD have received a huge amount of attention.…”
Section: Introductionmentioning
confidence: 99%